Impact of motivational interviewing on short-term changes in oral self-care behaviors in smokers - Isa Mohammadi- Zeidi,; Amir Pakpour Hajiagha (مجله دانشکده دندانپزشکی اصفهان, 2013)
Introduction: Given the strong association between smoking and periodontal disease, it is necessary that dentists place emphasis on smoking cessation in patients. Effectiveness of motivational interviewing in reducing plaque and improving self-care behaviors has been documented in previous studies. The aim of this study was to evaluate the effect of motivational interviewing on improving oral self-care behaviors in patients referring to dental clinics in Tonekabon, Iran.Materials and Methods: In the quasi-experimental study, 80 smoking patients referring to dental clinics in Tonekabon were randomly divided into experimental and control groups. The intervention consisted of two sessions of motivational interviewing for 30 minutes in 5-member groups, followed by follow-up by telephone in the experimental group. Data were collected before and 6 months after interviews using a questionnaire which included questions on demographic data, knowledge, attitude and an algorithm of stages of change, along with brushing and flossing behavior checklist. Finally, data were analyzed with SPSS 17.0, using chi-squared, Mann-Whitney, Wilcoxon tests, t-test and independent t-test. Results: The results showed significant increases in knowledge scores from 13.5 ± 5.6 to 21.6 ± 4.2 (p value < 0.001) and attitude scores from 32.40 ± 14.2 to 54.11 ± 15.9 (p value < 0.001) in the experimental group. It also significantly increased the number of patients in the active stages for smoking cessation, i.e. preparation (from 7.5 to 42.5 percent), action (from 0 to 25 percent) and maintenance (from 0 to 7.5 percent) (p value < 0.001). In addition, the experimental group exhibited improvements in self-care behaviors, including brushing (from 0.75 ± 0.20 to 1.19 ± 0.38, p value < 0.001) and flossing (p value < 0.001).Conclusion: Under the limitations of this study, it was shown that motivational interviewing is effective in promoting oral self-care behaviors among smoking patients referred to dental clinics. Key words: Motivational interviewing, Oral hygiene, Periodontal diseases, Smoking